Reconstruction of The Principle of Legal Certainty Fair Auction For Joint Assets After Divorce Decision - Jumanah, Jumanah; Hasan, KN Sofyan; Syaifuddin, Muhammad (SASI, 2023)
Introduction: This article is about analyzing the implementation of joint property auctions after a divorce decision that has not yet received fair legal certainty. The number of cases after the divorce decision results in the distribution of joint assets between the parties submitted to the Court after not getting peace in the distribution of joint assets, the Court can take over the matter by way of auction.Purposes of the Research: To analyze the principle of legal certainty in auctions in the implementation of auctions after divorce decisions in laws and regulations. Explain the legal problems in applying the legal principle of joint property auctions after the divorce decision. Finding reconstruction as the basis for setting up a bill on joint property auction laws after divorce decisions in the future.Methods of the Research: Based on hermeneutic paradigmatic which is based on philosophy and the scientific nature of law. This hermeneutic paradigm is carried out through a methodological strategy approach to learn from people, namely studying law by exploring and researching the meanings of law from the perspective of users or seekers of justice in the Religious Courts.Results of the Research: In the reconstruction of the principle of legal certainty in an equitable auction of joint assets after the divorce decision in future laws and regulations in legal considerations regarding joint assets that must be auctioned, through an auction procedure in accordance with applicable regulations.